Information system on tuberculosis: data completeness spatial analysis in the state of Paraná, Brazil - Marcelle Saldanha da Silva; Marcos Augusto Moraes Arcoverde; Rubia Laine de Paula Andrade; Adriana Zilly; Tereza Cristina Scatena Villa; Reinaldo Antonio Silva-Sobrinho (SciELO, 2021)
ABSTRACT Objective: To analyze the spatiality of completeness of the Information System on Diseases of Compulsory Declaration of tuberculosis in Paraná state, focusing on the border region. Method: A study composed by the notified cases of the disease treated in Paraná between 2008 and 2017. The variable completeness was classified as excellent (<5% of incompleteness), good (5 to <10%), regular (10 to <20%), poor (20% to 50%), and very poor (>50%). Moran global was used for the spatial correlation and local association was analyzed. Logistic regression was employed to assess the spatial association of the variables with the border and, for the significant variables, multiple logistic regression was used. The study abides by the resolution 510/2016 of the National Health Council. Results: There was a "high-high" correlation for education level, 2- and 6-month sputum smear in the Eastern health macroregional and "high-high" correlation in the Northwestern macroregional for 2-month sputum smear and antibiotic sensitivity testing. There was no spatial association with the border. Conclusion: Unsatisfactory completeness was identified in the database and conglomerates, indicating spatial association of incompleteness of some variables, but with no relation with the border. There was no worsening of completeness nor of the case outcomes related to these regions.